Analisis Hukum Ekonomi Syari’ah Terhadap Gugatan Wanprestasi Akad Murabahah Di Pengadilan Agama (Studi Perbandingan Pada Putusan Nomor 0945/Pdt.G/2014/ PA.ME dan Putusan Nomor 2370/Pdt.G/2016/PA.Pwt) - Muslim, Muslim; Syaiful, Dodi Alaska Ahmad; Melia, Maya (ASAS, 2021)
Defaults generally occur because one of the parties bound in the contract/agreement does not perform their obligations by not paying their debts on time, or paying improperly. Regarding the event of default, the aggrieved party can file a lawsuit with the Religious Courts. In tracing the researchers, two decisions related to the case of default on murabahah contracts at Bank Syari'ah were found, namely the Muara Enim Religious Court Decision Number 0945/Pdt.G/2014/PA.ME and the Purwokerto Religious Court Decision Number 2370/Pdt.G/ 2016/PA.Pwt, both of them tried the dispute over the default of the murabahah contract. This research is a library research (library research) with the nature of comparative descriptive-analytic research. This research was conducted by comparing the two decisions, then described and analyzed in depth using the theory of legal certainty and the theory of maslahah mursalah. The results of this study are, both the Muara Enim Religious Court and the Purwokerto Court, each use relatively the same legal basis in deciding cases of claims for default on murabahah contracts, namely based on contracts that have been made and signed by the contracting parties, then strengthened with the verses of the Koran, the Civil Code, KHES and laws, as well as other related regulations. Meanwhile, the calculation of the remaining debt and the remaining profit margin also uses the calculation of flat profits as a form of implementing Shari'ah principles, namely to ensure legal certainty and wider benefit.Keywords: murabahah, default, legal certainty, maslahah mursalah.